Cardiovascular risk factors in children and young adults born to preeclamptic pregnancies: a systematic review - Davis, Esther Frances; Lazdam, Merzaka; Lewandowski, Adam James; Worton, Stephanie Anne; Kelly, Brenda; Kenworthy, Yvonne; Adwani, Satish; Wilkinson, Andrew R; McCormick, Kenny; Sargent, Ian; Redman, Christopher; Leeson, Paul (Pediatrics (Evanston), 2012)
Preeclampsia is an independent cardiovascular risk factor for the mother, and recent studies reveal that offspring of affected pregnancies also may have an increased cardiovascular risk. Our objective was to examine evidence for increased cardiovascular risk factors in children exposed to preeclampsia in utero. We performed a systematic review and meta-analysis on studies reporting traditional cardiovascular risk factors in those exposed to preeclampsia compared to controls. Information was extracted on the classic cardiovascular risk factors, including blood pressure, lipid profile, glucose metabolism, and BMI from articles published between 1948 and August 2011 in Medline and Embase. Eighteen studies provided cumulated data on 45,249 individuals. In utero exposure to preeclampsia was associated with a 2.39 mm Hg (95% confidence interval: 1.74-3.05; P < .0001) higher systolic and a 1.35 mm Hg (95% confidence interval: 0.90-1.80; P < .00001) higher diastolic blood pressure during childhood and young adulthood. BMI was increased by 0.62 kg/m2 (P < .00001). Associations were similar in children and adolescents, for different genders, and with variation in birth weight. There was insufficient evidence to identify consistent variation in lipid profile or glucose metabolism. Young offspring of pregnancies complicated by preeclampsia already have increased blood pressure and BMI, a finding that may need to be considered in future primary prevention strategies for cardiovascular disease.